Do all Pediatric Urine Specimens Need to Go to the Laboratory? - Ali, Syed Rehan; Ahmed, Shakeel; Nizami, Sobia; Qadir, Maqbool (International Journal of Child Health and Nutrition, 2012)
Objective: This study aimed to evaluate the accuracy of the urine dipstick in diagnosing UTIs in children at a tertiary care centre in Pakistan. Methods: 72 inpatients at the Aga Khan Hospital pediatric ward, getting laboratory urinalysis due to UTI suspicion, were included. Dipstick tests were done on the urine samples being sent to the lab for microscopy. The sensitivity, specificity and likelihood ratios (LRs) of dipstick LE, and pyuria and bacteriuria on microscopy were calculated and compared, using urine culture results as the gold standard for diagnosis. Results: The specificity of dipstick LE, pyuria and bacteriuria were 77%, 77% and 90% respectively, while the positive likelihood ratios were was 28%, 44% and 49% respectively. Urine cultures were done for 58 patients, with 5 positive cultures, so plausible estimates of sensitivity were not made. Conclusions: Urine microscopy is a more accurate screening test for ruling in UTIs than the dipstick. Keeping in mind its diagnostic limitations, the dipstick can be used to help rule in a UTI, although confirmation by cultures is recommended. Further studies are needed to validate these results in children and to evaluate the dipstick’s sensitivity for ruling out disease.